THE EFFECT OF RECEIVABLES TURNOVER AND CASH TURNOVER ON RETURN ON ASSET (ROA) AT PT GAJAH TUNGGAL Tbk PERIOD 2013 – 2023 - Setiawati, Ica Indri; Nofiana, Lina (Journal of Research and Publication Innovation, 2024)
The aim of this research is to find out the influence of accounts receivable turnover and cash turnover on Return On Assets at PT Gajah Tunggal, Tbk from 2013 to 2023. Data analysis methods use Descriptive Statistical Tests, Classical Assumption Tests, Autocorrelation Tests, Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Correlation Coefficient Test, Determination Coefficient Test, t Test, and F Test. The research carried out by the author in preparing this thesis was descriptive and used quantitative methods. The population used is all annual financial reports of PT Gajah Tunggal, Tbk. The sample used in this research uses income statement and balance sheet data for the period 2013 - 2023. The results of the receivables turnover hypothesis test using the t test obtained a significant value of 0.00 < 0.05 so it can be said that receivables turnover has a partial effect on Return On Assets in PT Gajah Tunggal, Tbk from 2013 to 2023. The results of the cash turnover hypothesis test using the t test obtained a significant value of 0.03 < 0.05 so it can be said that cash turnover has a partial effect on Return On Assets at PT Gajah Tunggal, Tbk in 2013 until 2022. The results of the hypothesis test for receivables turnover and cash turnover using the F test obtained a significant value of 0.01 < 0.05 so it can be said that receivables turnover and cash turnover together influence Return On Assets at PT Gajah Tunggal, Tbk in 2013 until 2023.